2011
DOI: 10.3892/ijo.2011.1023
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial cancer cell response to combination therapy of gemcitabine and TRAIL

Abstract: Abstract. High-risk superficial urothelial carcinoma of the bladder (UCB) is commonly treated with intravesical bacillus Calmette-Guerin (BCG), but with significant side effects. We recently showed that the tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibited high therapeutic potential against UCB cells and with only limited toxic effects in normal cells. However, many cancer cells are refractory to TRAIL during monotherapy. Therefore, our experimental aim was to develop combinatorial app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, co-treatment of TRAIL with bortezomib increases anti-cancer effects through the overexpression of DRs in mammary carcinoma cells [34]. The combination of TRAIL with gemcitabine also synergistically increases anti-cancer effects through the expression of DRs in urothelial carcinoma cells [35]. Favokawain B (FKB) exerts a synergistic apoptotic effect when combined with TRAIL by increasing the expression of DR5 in prostate cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, co-treatment of TRAIL with bortezomib increases anti-cancer effects through the overexpression of DRs in mammary carcinoma cells [34]. The combination of TRAIL with gemcitabine also synergistically increases anti-cancer effects through the expression of DRs in urothelial carcinoma cells [35]. Favokawain B (FKB) exerts a synergistic apoptotic effect when combined with TRAIL by increasing the expression of DR5 in prostate cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, recombinant human TRAIL is being tested in phase I clinical trials [7]. Interestingly, TRAIL has been identified as the effector molecule in intravesical BCG immunotherapy [8] and TRAIL-based therapeutics have exhibited high therapeutic potential against bladder cancer cells in vitro [9,10], suggesting that TRAIL could be a suitable intravesical agent for the treatment of bladder cancer. However, recent studies have demonstrated that many types of cancer cells, including certain bladder cancer cell lines, are intrinsically insensitive to TRAIL [11].…”
Section: Introductionmentioning
confidence: 99%